The Puzzle of Metabolite Exchange and Identification of Putative Octotrico Peptide Repeat Expression Regulators in the Nascent Photosynthetic Organelles of Paulinella chromatophora - Oberleitner, Linda; Poschmann, Gereon; Macorano, Luis; Schott-Verdugo, Stephan; Gohlke, Holger; Stühler, Kai; Nowack, Eva C. M. (Frontiers in Microbiology, 2020)
The endosymbiotic acquisition of mitochondria and plastids more than one billion years ago was central for the evolution of eukaryotic life. However, owing to their ancient origin, these organelles provide only limited insights into the initial stages of organellogenesis. The cercozoan amoeba Paulinella chromatophora contains photosynthetic organelles - termed chromatophores - that evolved from a cyanobacterium ~100 million years ago, independently from plastids in plants and algae. Despite the more recent origin of the chromatophore, it shows tight integration into the host cell. It imports hundreds of nucleus-encoded proteins, and diverse metabolites are continuously exchanged across the two chromatophore envelope membranes. However, the limited set of chromatophore-encoded solute transporters appears insufficient for supporting metabolic connectivity or protein import. Furthermore, chromatophore-localized biosynthetic pathways as well as multiprotein complexes include proteins of dual genetic origin, suggesting that mechanisms evolved that coordinate gene expression levels between chromatophore and nucleus. These findings imply that similar to the situation in mitochondria and plastids, also in P. chromatophora nuclear factors evolved that control metabolite exchange and gene expression in the chromatophore. Here we show by mass spectrometric analyses of enriched insoluble protein fractions that, unexpectedly, nucleus-encoded transporters are not inserted into the chromatophore inner envelope membrane. Thus, despite the apparent maintenance of its barrier function, canonical metabolite transporters are missing in this membrane. Instead we identified several expanded groups of short chromatophore-targeted orphan proteins. Members of one of these groups are characterized by a single transmembrane helix, and others contain amphipathic helices. We hypothesize that these proteins are involved in modulating membrane permeability. Thus, the mechanism generating metabolic connectivity of the chromatophore fundamentally differs from the one for mitochondria and plastids, but likely rather resembles the poorly understood mechanism in various bacterial endosymbionts in plants and insects. Furthermore, our mass spectrometric analysis revealed an expanded family of chromatophore-targeted helical repeat proteins. These proteins show similar domain architectures as known organelle-targeted expression regulators of the octotrico peptide repeat type in algae and plants. Apparently these chromatophore-targeted proteins evolved convergently to plastid-targeted expression regulators and are likely involved in gene expression control in the chromatophore.